The importance of the dermatologist at the hospital A importância do dermatologista no ambiente hospitalar - Luciana Cirillo Maluf Azevedo; Carlos D' Aparecida Santos Machado Filho; Maura Simonetti Junqueira de Andrade; Alessandra Bunemer Nahas; Mellysande Pontes Faccin (Sociedade Brasileira de Dermatologia, 2012)
Skin lesions are often underestimated when patients are hospitalized in clinical or surgical areas. We made weekly visits to Mario Covas State Hospital of Sao Paulo, Brazil, for 35 weeks. Patients answered a questionnaire and underwent skin examination. The skin lesions were photographed. Of the 359 patients evaluated, a total of 1098 dermatological conditions were diagnosed. The most prevalent skin conditions included photodermatosis, neoplasms, vasculopathies and onychopathies. The growing number of dermatological diseases in hospitals justifies the active and constant presence of the dermatologist in a multidisciplinary team, thereby improving prognosis and patients' quality of life. As lesões dermatológicas costumam ser subestimadas quando da internação do paciente nas áreas clínica ou cirúrgica. Foram feitas visitas aos leitos do Hospital Estadual Mário Covas, do Estado de São Paulo - Brasil, durante 35 semanas. Os pacientes responderam um questionário e foram submetidos ao exame clínico dermatológico. As lesões cutâneas foram fotografadas. Nos 359 pacientes avaliados, foram encontrados 1098 diagnósticos dermatológicos. Os grupos mais prevalentes foram fotodermatoses, neoplasias, onicopatias e vasculopatias. O crescente número de afecções dermatológicas no ambiente hospitalar justificaria a presença mais ativa e constante do dermatologista na equipe multidisciplinar, melhorando o prognóstico e a qualidade de vida do doente.